Advancing Rheumatic Heart Disease Management in Indonesia: Strengthening Early Detection, Targeted Screening, and Prevention Strategies - Jochebet Irene; Ciho Olfriani (International Medical Journal Corp. Ltd, 2024)
Background: Indonesia ranks fourth globally in rheumatic heart disease (RHD) prevalence, with a mortality rate of 4.8 per 100,000—higher than malaria. Despite global progress in RHD management, Indonesia lacks a comprehensive national prevention program. Secondary prevention strategies could significantly improve outcomes in high-risk populations by targeting disease progression. Method: This systematic review and meta-analysis examined the impact of secondary prevention on echocardiographic outcomes in Indonesian RHD patients. The review included randomized controlled trials, observational studies, quasi-experimental designs, and case-control studies, emphasizing the role of secondary prevention in mitigating disease progression. Results: Six studies meeting inclusion criteria underwent full-text analysis, with four eligible for meta-analysis. These studies revealed that secondary prevention improved echocardiographic markers, demonstrating its potential to alter disease trajectories in resource-limited settings. Conclusion: Indonesia faces challenges in RHD management due to geographical and healthcare constraints. Echocardiographic screening, a sensitive and specific diagnostic tool, is vital for early detection and monitoring. With technological advancements, cost-effective screening is increasingly feasible, even in remote areas. Strengthening early detection, targeted screening, and secondary prevention strategies is critical for reducing the RHD burden in Indonesia.